The effect of ultrafine palm oil fuel ash (UPOFA) on chloride resistance of concrete - Lee, Siew Loung (2014)
In conjunction with the rapid development of palm oil industry, huge amount of waste generated which end up in landfill and extra cost paid to reduce its impact on our environment. Among the waste, the palm oil fuel ash (POFA) is well known as it contains pozzolanic property that has potential to promote the performance of concrete. Many researches had been carried out to study the mechanical performance of concrete containing POFA. In this study, the ultrafine palm oil fuel ash (UPOFA) was utilised in order to know its effect on the basic mechanical properties and corrosion resistance of blended concrete. The POFA was ground to reach median size of about 5 gm. Four mix of concrete was prepared by partially replacing 0 %, 10 %, 20 % and 30 % of Ordinary Portland Cement with UPOFA. All specimens were water cured for at least 28 days in water curing tank before subjected to lab tests. The specimens were tested for compressive strength, porosity and chloride resistance property through accelerated test and salt ponding. The accelerated chloride test employed was impressed voltage test, half-cell potential. Based on the test result, the concrete with 30 % of UPOFA content show better compressive strength, lower porosity and longer time to crack. It is found that the concrete with partial replacement of 30 % UPOFA to concrete also delays the corrosion to happen on steel bar through half-cell potential test. Besides, the concrete containing 30 % UPOFA as partial cement replacement shows lowest free and total chloride content at depth of 21 mm to 25 mm in concrete as compared to other specimen. From this study, the concrete with 30 % of UPOFA as partial cement replacement material shows the best basic mechanical property and chloride resistance.